Ganong's review of medical physiology - Barrett, Kim E.; Barman, Susan M.; Brooks, Heddwen L.; Boitano, Scott (Lange medical book, 2016)
For more than four decades, Ganong's Review of Medical Physiology has been helping those in the medical field understand human and mammalian physiology.